Pengaruh Pola Asuh Orang Tua terhadap Motivasi Belajar Siswa Kelas V SDN 2 Temulus Pada Masa Pandemi Covid-19 - Ahmad Sudi Pratikno; Clodia Cindi Aurora; Isna Ida Mardiyana (Universitas Negeri Makassar, 2022)
The purpose of this study was to determine the description of parenting styles and learning motivation of fifth-grade students at SDN 2 Temulus and to determine whether there is an influence of parenting styles on the learning motivation of fifth-grade students at SDN 2 Temulus. This study uses a quantitative approach. The sample in this study used a saturated sampling technique, which took the entire population as a sample with a total of 28 fifth-grade students. The data collection technique used questionnaires and documentation, the data collection instrument used a parent and student questionnaire sheet, and the data analysis technique used quantitative analysis using the SPSS application. The results showed that the parenting style mostly used by fifth-grade parents at SDN 2 Temulus was democratic parenting with a percentage of 82%. The percentage of learning motivation of fifth-graders at SDN 2 Temulus is mostly in the